Proposal of the readout electronics for the WCDA in the LHAASO experiment - 赵雷 刘树彬 安琪 (Chinese physics C, 2014)
The LHAASO （Large High Altitude Air Shower Observatory） experiment is proposed for a very high energy gamma ray source survey, in which the WCDA （Water Cherellkov Detector Array） is one of the major coinponents. In the WCDA, a total of 3600 PMTs are placed under water in four ponds, each with a size of 150m×150 m. Precise time and cimrge measurement is required for the PMT signals, over a large signal amplitude range from a single P.E. （photo electron） to 4000 P.E. To fulfill the high requirement of a signal measurement in so many front end nodes scattered in a large area, special techniques are developed, such as multiple gain readout, hybrid transmission of clocks, commands and data, precise clock phase alignment and new trigger electronics. We present the readout electronics architecture for the WCDA and several prototype modules, which are now being testedin the laboratory.